Functional outcome of unstable intertrochanteric fracture treated with proximal femoral nail - Dev Sharma, Bishnu; Raj Shrestha, Sujit; Prakash Dawadi, Tej; Rijal, Sanjeeb; KC, Saugat (Journal of Chitwan Medical College, 2024)
Background: Intertrochanteric fractures are common in elderly with osteoporotic bones. Unstable fractures are the one which cause problem and complication rates are higher with conventional fixation devices. Proximal femoral nail is now the preferred implant for the treatment of intertrochanteric fractures. This study aims to evaluate the functional outcome of proximal femoral nail in unstable intertrochanteric fractures in our setting. Method: This prospective study conducted at Chitwan Medical College from Jan 2021 to Dec 2022 included 35 patients aged >18 years having unstable intertrochanteric fractures who consented to participate in the study. Excluded were those with open fracture, polytrauma or pathological fracture. All patients were treated with long proximal femoral nail and followed-up for a minimum of one year. Clinical assessment was done using Harris Hip Score along with radiological evaluation for fracture union. Data analysis was done using Statistical Package for Social Sciences. A p<0.05 was considered statistically significant. Result: There were 16 males and 19 females with mean age of 70.7±15.2 years among which 23 had AO Foundation/Orthopaedic Trauma Association type 31A2 and 12 had 31A3 fractures. Majority sustained injury from trivial fall 18(51.4%). All fractures united at a mean of 16.9±3.7 weeks with the final Harris Hip Score as excellent in 10(28.6%) and good in 19(54.3%). Pre-injury ambulatory status was regained by 26(74.3%) patients. The overall complication rate was 9(25.7%). Conclusion: Proximal femoral nails provide adequate fixation for unstable intertrochanteric fractures with good functional outcome.